Integrated distribution network expansion planning incorporating distributed generation considering uncertainties, reliability, and operational conditions - Bagheri, A.; Monsef, H.; Lesani, H. (International journal of electrical power & energy systems, 2015)
•An integrated DNEP is proposed considering renewable and non-renewable DGs.•Reliability and operational considerations are regarded.•Uncertainties of wind energy, load demand, and energy price have been considered.•Possibility of islanding has been regarded in reliability evaluation.•Required conditions for safe islanding considering all the uncertainties have been checked out. In this paper, an integrated methodology is proposed for distribution network expansion planning which considers most of the planning alternatives. The planning aims to determine the optimal reinforcement of existing medium voltage lines and high voltage/medium voltage substations, or installation of new ones to meet the load growth in the planning horizon subject to the technical and operational constraints. Also, to take the advantages of new technologies, the renewable and non-renewable distributed generations have been included in the problem as another alternative. The uncertainties related to renewable DGs, load demand, and energy price have been considered in the calculation of cost components. The load duration curve has been utilized for loads such that the results be more precise. The possibility of islanding and load transferring through the reserve feeders have been regarded in the problem to improve the reliability of the network. Also, the required condition for successful and safe operation of island considering all of uncertainty states have been checked out to accurately calculate the reliability. The genetic algorithm is employed to solve this integrated problem. Finally, the proposed method is applied to the 54-bus system and also a real large-scale distribution network, and the results are discussed. The results verify the effectiveness of the presented method.